Textile reinforced mortars (TRM) for repairing and retrofitting masonry walls subjected to in-plane cyclic loads. An experimental approach. (15th March 2021) - Torres, Benjamín; Ivorra, Salvador; Javier Baeza, F.; Estevan, Luis; Varona, Borja
Highlights: Effectiveness of TRM in repairing damaged masonry walls under in-plane cyclic loads. Three full scale masonry walls have been constructed, repaired, reinforced and re-tested. The higher ductility associated with TRM was observed in the cumulative energy loss. TRM reinforcement could guarantee the structural stability. TRM layers modified the stiffness variations, strength and the cracking pattern. Abstract: Masonry walls exhibit low tensile strength and high material heterogeneity, which makes them especially vulnerable against cyclic loading conditions, such as those typical in earthquakes. This paper presents the experimental results obtained from tests on three masonry walls reinforced with textile reinforced mortar (TRM) materials subjected to in-plane cyclic loading. These full-scale masonry walls were tested in the LARGE laboratory at the University of Alicante (Alicante, Spain). The walls had been built using a traditional construction technique, with solid clay bricks layered with lime mortar. One specimen was tested and damaged by in-plane cyclic loading and was subsequently strengthened by a vertical layer of TRM with an overlapping of 200 mm. It was then tested again until failure in a second test. In addition, another undamaged specimen had been previously reinforced with the same TRM technique and tested until failure, thus providing a third test. A network of sensors and digital image correlation systems were used to monitor displacements and crack patterns. The comparison between these experimental results made it possible to assess the effectiveness of TRM in restoring the structural integrity of damaged masonry walls and almost doubling their load-bearing capacity under cyclic loads. Conclusions obtained here provide valuable information to the scientific community, architects and structural engineers about the strengthening and repair of severely damaged masonry walls.